Revisiting the History of Chagas Disease: "Live to tell" - Cunha,Ademir Batista da (2022)
Abstract In 1907, Carlos Chagas was designated to fight paludism in the Rio das Velhas region along the Central do Brasil railroad. During his field research, Chagas discovered a hematophagous insect ( Panstrongylus megitus ) carrying a new trypanosomatide, which he named Trypanosoma cruzi . On April 14th, 1909, he found the same parasite in the blood of a febrile child, submitting the announcement of his discoveries to the Brasil Médico scientific journal. Here, we discuss the early stages in the establishment of a new human morbid entity during the first decades after its discovery with a definite influence from its discoverer, Carlos Chagas, as well the first collaborators. Moreover, we cover the importance of the Center for the Study and Prophylaxis of Chagas Disease in Bambuí (MG), unraveling the most advanced developments in research within the disease’s habitat and the widening perspectives for modern research that have emerged after the 1960s and continue to improve to this day. In this revisitation to the history of Chagas disease, we begin at Manguinhos (RJ ), making our way to Lassance (MG), where the discovery took place. Then, we travel back to Rio de Janeiro in the beginning of the twentieth century and Brazilian republic until the current day, revealing milestone publications that settled Chagas disease both as a source of pride for Brazilian medicine and as a challenge with important aspects that remain to be clarified. Any similarities to our country’s politics and economy in the twentieth century are not mere coincidences.